THE ADOPTION OF GOOD CORPORATE GOVERNANCE PRINCIPLES HEIGHTEN MOMENTUM ON EMPLOYEE COMMITMENT - May1, Amy Yeo Chu; Qi, Ngo Jia; Rudiawarni, Felizia Arni (Graduate Program of Universitas Tarumanagara, 2023)
Literature has unfolded that employee commitment has proven to be of great influence on workplace performance and productivity. This study therefore aims to investigate if corporate governance principles affect the employee commitment with corporate reputation and organisational trust mediating the dual relationship. A positivist approach using survey method was employed to collect data from employees working in Malaysian companies. A total of 230 sample were analysed using SPSS and Smart PLS. The results show a positive relationship between corporate governance principles and employee commitment as well as corporate reputation. Corporate governance also had a significant effect on organisation trust which in turn leads to employee commitment. The mediating effect of both corporate reputation and organisational trust had strengthened the relationship between the two constructs. upending the wave of employee commitment in human resource research, these findings implied that governance concepts such as fairness, accountability, responsibility, and transparency had positive impact on employee commitment as well. Future research to close the gap also has been highlighted.